Rendu-Osler-Weber Disease with High Pulmonary Hypertension and Interstitial Lung Disease - Yu. A. Lutokhina; O. V. Blagova; P. O. Savina; E. V. Zaklyazminskaya (Рациональная фармакотерапия в кардиологии)
A 64-year-old female with a family history of hereditary hemorrhagic telangiectasia (HHT) was hospitalized due to complaints of dyspnea during light physical exertion and leg edema. HHT was diagnosed at 20 y.o., recurrent nasal bleeding started at age 52, bleedings severity was aggravated by not completely compensated hypertension. At the age of 60, after a massive hemorrhage, she noted the onset of dyspnea, edema, ascites. Diuretics and iron preparations improved her well-being, but from that period onward her heart failure worsened after each massive blood loss. The last major bleeding was before the present hospitalization (Hgb 67 g/l), after which heart failure symptoms significantly deteriorated. Echocardiography showed preserved left ventricular ejection fraction, but revealed high pulmonary hypertension (systolic pulmonary artery pressure 69 mmHg). Chest computed tomography (CT) with contrast showed no evidence of pulmonary embolism, but interstitial lung lesions were detected. Pulse therapy with glucocorticosteroids did not result in positive dynamics at the control CT scan, which allowed to reject a separate interstitial lung disease. As a result of cardiotropic and diuretic therapy, as well as correction of anemia, the patient's condition improved. Macitentan was administered, but the patient refused from it because one of possible side effects was anemia. A year later the patient diedfrom acute progression of pulmonary hypertension. According to the literature, pulmonary hypertension in HHT can have a significant impact on the prognosis and requires timely diagnosis and treatment. Interstitial lung lesions are a manifestation of the underlying disease and does not require special treatment.